Analysis of long term responses and their impact on outcomes in patients with chronic phase CML treated with four different TKI modalities – analysis of 5 prospective clinical trials - Jain, Preetesh (Lancet Haematol, 2015)
BACKGROUND: Several tyrosine kinase inhibitors (TKI) are available for treatment of patients with chronic myeloid leukemia in chronic phase (CML-CP). We analyzed long term response and compared outcomes of patients treated with 4 TKI modalities used as frontline therapy for CML-CP. METHODS: This is a retrospective cohort analysis of 482 patients with chronic phase CML treated in prospective clinical trials with frontline TKI modalities at a single institution. Patients were treated with imatinib 400 mg daily (n=68), imatinib 800 mg daily (n=200), dasatinib 50 mg twice daily or 100 mg daily (n=106) or nilotinib 400 mg twice a day (n=108). Primary end point of the study was to determine whether achieving complete cytogenetic response (CCyR) or major molecular response (MMR) has comparable prognostic implications regardless of the type of frontline TKI modality. Intention to treat analyses were performed for each TKI modality for response assessment and survival endpoints were analyzed using the Kaplan-Meier method and differences calculated by the log-rank test. Univariate and multivariate analyses were performed using the Cox proportional hazard regression. FINDINGS: Overall, higher proportions of patients receiving imatinib 800 and 2(nd) generation TKI achieved complete cytogenetic response (CCyR), major molecular response (MMR) and ≥4.5 log reduction in BCR-ABL transcripts (MR(4.5)) at all time-points (3–60 months). Disease transformation occurred in 35/482 patients (7%), events occurred in 76/482 (16%) and 53/482 patients (11%) died. Overall, 5 year outcomes were event-free survival (EFS) 84%, failure-free survival (FFS) 70%, transformation-free survival (TFS) 92%, and overall survival (OS) 93%. Compared to other 3 treatment modalities, patients treated with imatinib 400 had significantly inferior EFS, FFS and TFS. Multivariate analysis demonstrated that therapy with imatinib 800, dasatinib or nilotinib predicted for EFS while FFS, TFS and OS were similar irrespective of the TKI used. INTERPRETATION: Treatment with imatinib 800, dasatinib or nilotinib demonstrates superior rates of responses, which are maintained even at longer follow up (5 years). Patient outcomes are improved after treatment with imatinib 800 and 2(nd) generation TKI’s as compared to imatinib 400. Results with imatinib 800 are similar to 2(nd) generation TKI with higher rate of discontinuation.